Sustainable artificial intelligence: A~corporate culture perspective - Carmen Isensee; Kai-Michael Griese; Frank Teuteberg (Sustainability Management Forum, 2022)
In recent years, various studies have highlighted the opportunities of artificial intelligence (AI) for our society. For example, AI solutions can help reduce pollution, waste, or carbon footprints. On the other hand, there are also risks associated with the use of AI, such as increasing inequality in society or high resource consumption for computing power. This paper explores the question how corporate culture influences the use of artificial intelligence in terms of sustainable development. This type of use includes a~normative element and is referred to in the paper as sustainable artificial intelligence (SAI). Based on a~bibliometric literature analysis, we identify features of a~sustainability-oriented corporate culture. We offer six propositions examining the influence of specific manifestations on the handling of AI in the sense of SAI. Thus, if companies want to ensure that SAI is realized, corporate culture appears as an important indicator and influencing factor at the same time.
Keywords: 650; Sustainability; SDG; AI; Sustainable AI; Organizational culture; Corporate culture; Nachhaltigkeit; SDG; KI; Nachhaltige KI; Organisationskultur; Unternehmenskultur